Palabras porteñas : una laudatio al Prof. Dr. Paulo Benavides : obertura sobre naturaleza y cultura en nuestro jurista Decano - Ferreyra, Raúl Gustavo (2013)
"Written version of the oral presentation given on October 1, 2013, during the awarding of the honorary doctorate from the University of Buenos Aires to Paulo Bonavides. The ceremony took place in the Red Room of the Faculty of Law."